Analisis Laporan Realisasi Anggaran untuk Menilai Kinerja Keuangan Pemerintah Provinsi DKI Jakarta Tahun 2021-2023 - Widodo, Anggoro Adji; Dwi Ajeng Riyanti; Firda Rahma Dani; Meila Eka Abdillah; Sonny Fransisco Siboro (CV. KAMPUS AKADEMIK PUBLISING, 2025)
One of the most critical components in regional governance is local government finance. District or city governments are required to submit reports on their financial accountability to evaluate their performance in carrying out their duties. A tool that can be used to assess the financial performance of local governments is by calculating financial ratios from the budget realization reports. This study aims to analyze whether the budget realization performance aligns with the established development goals and priorities and to detect potential deviations or wasteful spending in the DKI Jakarta province during the 2021–2023 period. The data used is secondary data sourced from the annual financial reports of the DKI Jakarta Provincial Government from 2021 to 2023. The method applied is quantitative descriptive analysis, focusing on the Budget Realization Report (LRA) found in the Regional Government Financial Report (LKPD) of the DKI Jakarta Province, particularly in the expenditure analysis aspect. The research results indicate that the financial performance has an independence ratio categorized as participatory, an effectiveness ratio categorized as fairly effective, an efficiency ratio categorized as less efficient. Therefore, it is recommended that the DKI Jakarta Provincial Government allocate regional spending proportionally, explore the potential of regional original income, and enhance supervision over the use of the State Budget (APBD).